2017
DOI: 10.1093/hmg/ddx399
|View full text |Cite
|
Sign up to set email alerts
|

Bardet–Biedl syndrome-8 (BBS8) protein is crucial for the development of outer segments in photoreceptor neurons

Abstract: Bardet-Biedl syndrome (BBS) is an autosomal recessive ciliopathy characterized by developmental abnormalities and vision loss. To date, mutations in 21 genes have been linked to BBS. The products of eight of these BBS genes form a stable octameric complex termed the BBSome. Mutations in BBS8, a component of the BBSome, cause early vision loss, but the role of BBS8 in supporting vision is not known. To understand the mechanisms by which BBS8 supports rod and cone photoreceptor function, we generated animal mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
56
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 44 publications
7
56
2
Order By: Relevance
“…Mutations in genes encoding the anterograde motor, kinesin-2 (e.g. Marszalek et al, 2000;Lopes et al, 2010), IFT20 (Keady et al, 2011), IFT88 (Pazour et al, 2002), IFT140 (Crouse et al, 2014), IFT122 (Boubakri et al, 2016), IFT57 (Krock and Perkins, 2008), and the BBS proteins, BBS2 (Nishimura et al, 2004), BBS3 (Zhang et al, 2011), BBS4 (Abd-El- Barr et al, 2007), BBS6/MKKS (Ross et al, 2005) and BBS8 (Hsu et al, 2017;Dilan et al, 2018) have all been shown to affect RHO delivery, outer segment formation and maintenance, and typically result in photoreceptor degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in genes encoding the anterograde motor, kinesin-2 (e.g. Marszalek et al, 2000;Lopes et al, 2010), IFT20 (Keady et al, 2011), IFT88 (Pazour et al, 2002), IFT140 (Crouse et al, 2014), IFT122 (Boubakri et al, 2016), IFT57 (Krock and Perkins, 2008), and the BBS proteins, BBS2 (Nishimura et al, 2004), BBS3 (Zhang et al, 2011), BBS4 (Abd-El- Barr et al, 2007), BBS6/MKKS (Ross et al, 2005) and BBS8 (Hsu et al, 2017;Dilan et al, 2018) have all been shown to affect RHO delivery, outer segment formation and maintenance, and typically result in photoreceptor degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulation of IS proteins STX3 and STXBP1 in the OS has been described in all BBS mouse models examined and in Cep290 mutant mice (30)(31)(32)40). Mislocalization of these proteins was evident as early as at P13 (the youngest age examined) in Lztfl1 gt/gt mice and observed throughout the length of the OS (Figure 2D), indicating that the pathogenic process begins before or when the OS begins to elongate.…”
Section: Natural History Of Retinal Degeneration In Lztfl1 Gt/gt Micementioning
confidence: 76%
“…Ablation of BBS gene function causes disc morphogenesis defects and disorganization of the OS ultrastructure (30)(31)(32). We examined whether restoring Lztfl1 expression at P5-12 could preserve the OS ultrastructure, using transmission electron microscopy (TEM) (Figures 3H and S4).…”
Section: Restoration Of Lztfl1 Expression At Very Early Degeneration mentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulation of STX3 and STXBP1 in the outer segment is a phenotype commonly observed in BBS mutant photoreceptors [45][46][47]. While CEP290 is a stationary protein constituting the ciliary gate, BBSomes (a protein complex composed of 8 BBS proteins [56,57]) are adapter complexes that link ciliary cargos to IFT particles and transport them in and out of the ciliary compartment [58][59][60][61][62][63][64][65].…”
Section: Mislocalization Of Inner Segment Membrane Proteins In Cep290mentioning
confidence: 99%